Analisa Proyek Pengembangan Sistem Informasi Perpustakaan Umum Menggunakan Unified Modeling Language - Nurseptaji, Adi; Adamsyah , Agusdael; Wildan , Mochamad; Akmal, Muhamad; Ardiansyah , Pyan; Firmansyah , Ricky (JUSS (Jurnal Sains dan Sistem Informasi), 2020)
The library is an important facility as a source of information, especially in the world of education to support learning activities for students and knowledge seekers to add insight and knowledge. To facilitate and accelerate library services, a Library Information System is needed in order to increase productivity, effectiveness and efficiency in the library. For the development stage of the library information system using the Unified Modeling Language (UML) as a tool for modeling and documenting the Library Information System. With the Public Library Information System Development Project Analysis Using the Unified Modeling Language, it is hoped that it can improve service, productivity, effectiveness and efficiency in libraries to increase reading interest for students and facilitate and speed up the transaction process of borrowing and returning books to the library.